EDUKASI DAN PENGETAHUAN TERHADAP PENTINGNYA KARAKTERISTIK BERWIRAUSAHA - Indriyarti, Eko Retno; Murtiningsih, Retno Sari; Tribudhi, Debbie Aryani (Jurnal Pengabdian dan Kewirausahaan, 2023)
Individual entrepreneurial characteristics, especially as seen from generation to generation, have distinct differences. For example, the younger generation has entrepreneurial characteristics such as wanting to succeed quickly, focusing on instant processes, and easily "following along" with existing trends. This is the primary concern of the implementing team, and it necessitates additional knowledge in developing entrepreneurial characteristics. This training was provided to 20 partner participants from the Amanah Cordova Entrepreneurship School in Pondok Jati Village, South Tangerang. This activity took place on December 11, 2022 and was carried out through face-to-face discussions. This activity's outcomes focused on three key areas: the quality of the material provided, the quality of the activity process, and the quality of the resource persons. According to the indicators of the quality of the material provided, the participants thought the material was good enough to be used later in entrepreneurship. Furthermore, the participants felt that the activity was going well overall, based on the quality of the activity process indicators, and that it was able to provide them with additional knowledge about the characteristics of entrepreneurship. The good manner and attitude of the resource persons in conveying the material was an important point that was highly rated by all participants in terms of the quality of the resource persons. Characteristic formation and improvement are dynamic, mirroring the dynamics of business competition. As a result, this activity can be performed on a regular and continuous basis.